2013
DOI: 10.1038/ejhg.2013.99
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental disorders among individuals with duplication of 4p13 to 4p12 containing a GABAA receptor subunit gene cluster

Abstract: Recent studies have shown that certain copy number variations (CNV) are associated with a wide range of neurodevelopmental disorders, including autism spectrum disorders (ASD), bipolar disorder and intellectual disabilities. Implicated regions and genes have comprised a variety of post synaptic complex proteins and neurotransmitter receptors, including gamma-amino butyric acid A (GABA A ). Clusters of GABA A receptor subunit genes are found on chromosomes 4p12, 5q34, 6q15 and 15q11-13. Maternally inherited 15q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…In the leukocyte transendothelial migration pathway, the TXK gene, which is a non-receptor tyrosine kinase (with altered expression in ASD, ear infection, IBD, and bacterial and viral infections), specifically regulates IFN- γ gene transcription and the development, function, and differentiation of conventional T cells and nonconventional NKT cells. Mutation of the TXK gene has been identified to be a segregating factor for a number of neurodevelopmental disorders, including ASD, bipolar disorder, and intellectual disabilities [50]. …”
Section: Resultsmentioning
confidence: 99%
“…In the leukocyte transendothelial migration pathway, the TXK gene, which is a non-receptor tyrosine kinase (with altered expression in ASD, ear infection, IBD, and bacterial and viral infections), specifically regulates IFN- γ gene transcription and the development, function, and differentiation of conventional T cells and nonconventional NKT cells. Mutation of the TXK gene has been identified to be a segregating factor for a number of neurodevelopmental disorders, including ASD, bipolar disorder, and intellectual disabilities [50]. …”
Section: Resultsmentioning
confidence: 99%
“…In addition, there is strong evidence for transcriptional regulation of GABA A R subunits by neurosteroids, as well as in a number of pathological conditions, including epilepsy, ethanol intoxication, Alzheimer's disease, and schizophrenia [reviewed in Steiger & Russek (2004) and Grabenstatter et al (2012)]. A recent genetic study identified a chromosomal duplication in a locus encoding four GABA A R subunits (4p12: a2, a4, b1, and c1) that is associated with neurodevelopmental disorders (Polan et al, 2013). In contrast, it is not well established whether the compensatory increase in subunit expression observed in some GABA A R subunit-KO mice (Box 1) reflects transcriptional control or is attributable to changes in mRNA stability and/or post-translational mechanisms (Peng et al, 2002;Kralic et al, 2006;Ogris et al, 2006).…”
Section: Transcriptional Control Of Gaba a R Subunit Expressionmentioning
confidence: 99%
“…First, additional molecular functional studies are needed to investigate the detailed biochemical mechanisms of the genetic effects found in this study. As identified in a recent genetic study, duplication of a cluster of four GABA A receptor genes located on chromosome 4p12 (i.e., GABRB1, GABRA4, GABRA2, GABRG1) was associated with neurodevelopment disorders (Polan et al, 2014). Due to the implications of GABRB1 in clinical samples characterized by reduced thalamus volume and abnormal intellectual performance, future research should explore potential associations between these GABA A receptor genes and thalamus volume and their interaction effect on intelligence in clinical samples, such as those with alcohol dependence, bipolar disorder, and schizophrenia.…”
Section: Discussionmentioning
confidence: 96%